Effectiveness of Thermal Properties in Thermal Energy Storage Modeling - Torres Sevilla, Law; Radulovic, Jovana (Frontiers in Mechanical Engineering, 2021)
This paper studies the influence of material thermal properties on charging dynamics in a low temperature TES which combines sensible and latent heat. The analysis is based on a small scale packed bed with encapsulated PCM, numerically solved using COMSOL Multiphysics. The PCMs studied are materials constructed on typical thermal properties (melting temperature, density, specific heat capacity (solid and liquid), thermal conductivity (solid and liquid) and the latent heat) of storage mediums in literature. The temperature change is monitored at three different positions along the tank. Results indicate that latent heat is a leading parameter in the performance of the system, and that the thermal properties of the PCM in liquid phase influence the overall heat absorption more than its solid counterpart.